Evaluating the land use patterns of medium-sized Hellenic cities. Issue 2 (3rd May 2016) - Tsilimigkas, Georgios; Stathakis, Demetris; Pafi, Maria
Abstract : Land use morphology has profound effects both on city functions and peri-urban areas. They can either lead to conflicts with negative side effects or generate positive synergies. This study focuses on land use spatial configurations and interprets the interactions among them. In order to evaluate spatial planning policies, the measurement of urban land use patterns is considered to play an important role in the urban development process and deserves further attention. A comparative analysis of the land use patterns of the medium-sized Hellenic cities is attempted, there are also used using pre-existing metrics, some new data from the European Environment Agency Urban Atlas 2006 geodataset and population and construction census data concerning the last decade from the national Hellenic Statistical Authority data set. The Larger Urban Zones of the medium-sized Hellenic cities are chosen as a suitable study level based both on population size and socio-spatial procedures. The results provide interesting information about the diversification among medium-sized cities, while some particularities concerning urban procedures appear to emerge for some of them. Many discussion points arise from this study concerning the data availability, the method, the functional city area delineation and the Larger Urban Zones definition.